1995
DOI: 10.1183/09031936.95.08071136
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis on small cell lung cancer and non-small cell lung cancer by means of NSE and CYFRA-21.1

Abstract: D Di is sc cr ri im mi in na an nt t a an na al ly ys si is s o onThe variables selected were NSE and CYFRA-21.1. Considered together, they were able to give a 97% rate of correct classification. The formula generated (canonic variable, CV) was validated on a group of seven SCLC and 22 NSCLC patients. Only two errors occurred.We therefore conclude that the canonic variable tested, based on NSE and CYFRA-21.1, provides a good discrimination between the two types of lung cancer. The method is rapid, relatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 20 publications
1
20
2
1
Order By: Relevance
“…The present study ited (Stieber et al, 1993;Ebert et al, 1995;Paone et al, suggests that the determination of CYFRA 21-1 may provide Wieskopf et al., 1995), it is worthwhile investigating additional, independent, prognostic information in squaer pretreatment CYFRA 21-1 concentrations are mous-cell lung cancer patients. related to the likelihood of relapse in lung cancer patients who undergo curative resection.…”
Section: Discussionsupporting
confidence: 52%
“…The present study ited (Stieber et al, 1993;Ebert et al, 1995;Paone et al, suggests that the determination of CYFRA 21-1 may provide Wieskopf et al., 1995), it is worthwhile investigating additional, independent, prognostic information in squaer pretreatment CYFRA 21-1 concentrations are mous-cell lung cancer patients. related to the likelihood of relapse in lung cancer patients who undergo curative resection.…”
Section: Discussionsupporting
confidence: 52%
“…This approach permitted generating a score able to correctly classify 95.9% of patients with an error rate of 8.3% in SCLC and 2.7% in NSCLC subjects. The formula to calculate this score was the following (Paone et al, 1995): The encouraging results obtained in the previous investigation led to the present study with the aim of: (1) verifying whether the above score showed the same discriminating power in a larger group of patients; and (2) analysing its reliability in different subgroups of lung cancer patients. antigen, produced by Byk Sangtec, Cormano, Italy; normal values less than 95 U ml-'); (3) CYFRA-21 .1 (a cytokeratin antigen, by CIS Diagnostici, Vercelli, Italy; normal values less than 3.3 ng ml-'); and (4) NSE (neuron-specific enolase, by CIS Diagnostici; normal values less than 12.5 ng ml-').…”
mentioning
confidence: 99%
“…Similar studies have shown that increasing the number of samplings (repeated sampling in several sessions) significantly increases the sensitivity of mRNA biomarkers [29] [30]. This indicates that the odds of detecting markers are lower in a single sampling.…”
Section: Discussionmentioning
confidence: 53%
“…A number of nonsmall cell lung cancer patients who are recognized in primary stages of the disease and undergo surgery die due to tumor recurrence, which shows presence of undetectable metastasis at the time of surgery. These laboratory findings show that the currently used staging system does not have sufficient sensitivity for compartmentalization of cancer patients [30] [31].…”
Section: Discussionmentioning
confidence: 97%